1997
DOI: 10.1046/j.1537-2995.1997.37197176951.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performances of enzyme‐linked immunosorbent, western blot, and polymerase chain reaction assays for human T‐lymphotropic virus type II infection that is endemic among Indians of the Gran Chaco region of South America

Abstract: The sensitivities of the tested HTLV serologic assays were comparable. However, the specificity of the Retrotek ELISA was significantly lower than that of the others. When positive, the subtyping assays were very specific. However, PCR assays would seem preferable or to be a necessary adjunct for the sensitive detection of HTLV-IIB infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…0931-1793/99/4608-05514114.00/0 Do1.z and MORENO positive reactions in WB supports the use of this assay as a reference test for the validation of ELISA for the diagnosis o f BLV-infections. Similar conclusions with other retroviral systems havc been reached (Poiesz e t al., 1997). The intcntion of this work was t o develop a simple, specific and sensitive ELISA for the detection of antibodies from naturally BLV-infected bovines, using WR as confirmatory test.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…0931-1793/99/4608-05514114.00/0 Do1.z and MORENO positive reactions in WB supports the use of this assay as a reference test for the validation of ELISA for the diagnosis o f BLV-infections. Similar conclusions with other retroviral systems havc been reached (Poiesz e t al., 1997). The intcntion of this work was t o develop a simple, specific and sensitive ELISA for the detection of antibodies from naturally BLV-infected bovines, using WR as confirmatory test.…”
Section: Introductionsupporting
confidence: 87%
“…This is of remarkable importance in herds which had been tested repeatedly for some time by AGIDT (Manz and Bauer, 1985), and might be relevant in countries, where the management of cattle and the presence of bloodsucking vectors promote the spreading and maintenance of blood-transmitted viral diseases (Ferrer, 1980). In retroviral infections, the enzyme-linked immunosorbent assay (ELISA) has been used mainly as a screening test, whereas western blotting (WF3) has been chosen as reference confirmatory assay (Poiesz et al, 1997). In ELISA the non-specific reactions are relatively common and difficult to distinguish from specific ones, whereas in WB the detection of antibodies against the individual viral proteins allows the resolution of specific from nonspecific reactions (Sherman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…PCR methods (in‐house methods as well as commercially available tests) have been useful to discriminate between HTLV‐I and HTLV‐II infections and resolve infection status of individuals with an indeterminate WB 5,6,12,15,22,26‐30 . Some studies have indicated that the sensitivity for detection of HTLV‐II infection by PCR is lower than that of the serologic methods, 28,30 whereas other studies have indicated that the prevalence of HTLV infection is underestimated by serologic methods in comparison with PCR 6,31,32 …”
mentioning
confidence: 99%